2016
DOI: 10.1097/md.0000000000002590
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Surgical Outcomes in Patients With Intermittent Exotropia

Abstract: The clinical characteristics and surgical outcomes in a large sample of patients with intermittent exotropia (IXT) as well as an analysis of risk factors associated with surgical failures are presented in this article. Data from IXT patients who received surgical management at the Eye Hospital, in the Zhongshan Ophthalmic Center, of Sun Yat-Sen University, China from January 2009 to December 2013 were reviewed retrospectively. Included within this analysis were data from pre- and postoperative ocular motility,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
44
2
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 29 publications
2
44
2
1
Order By: Relevance
“…The outcome of strabismus surgery in Asian countries has been reported by researchers in Thailand, Korea, Hong Kong and China [3][4][5][6][7][8]. However, apart from Thailand, we found no other data from South East Asian countries [3].…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…The outcome of strabismus surgery in Asian countries has been reported by researchers in Thailand, Korea, Hong Kong and China [3][4][5][6][7][8]. However, apart from Thailand, we found no other data from South East Asian countries [3].…”
Section: Introductionmentioning
confidence: 54%
“…Reported success rates of strabismus surgery vary widely, ranging from 35.6 to 80.5% [3][4][5][6][7][8].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, delaying the surgery should not influence the sensory and visual outcomes to a great extent, and many studies have advocated for a delayed approach as it may also allow for more accurate measurements and better results. [19][20][21][22][23][24][25][26][27][28][29][30][31][32][33]: Distance stereopsis is affected earlier in X(T) compared with near stereopsis. Some investigators advocate the use of distance stereoacuity to monitor the progression of distance, indication for surgery and as an outcome measure.…”
Section: Age Factor [13-18]mentioning
confidence: 99%
“…The most common treatment strategy for strabismus is the surgical manipulation of specific extraocular muscles to re-align the eyes. Although popular and practiced widely, studies have shown that surgical approaches have varying levels of success and permanence, and often the patients tend to regain misalignment leading to multiple surgeries (Pineles et al 2010, Yang et al 2016). Ekdawi and colleagues suggested that the failure rate of surgical correction in children with intermittent exotropia rises to 84% by 15 years (Ekdawi et al 2009).…”
Section: Introductionmentioning
confidence: 99%